2019
DOI: 10.3390/biomimetics4040072
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mixed Flow Fans with Bio-Inspired Grooves

Abstract: Mixed flow fan is a kind of widely used turbomachine, which has faced problems of further performance improvement in traditional design methods in recent decades. Inspired by the microgrooves such as riblets and denticles on bird feathers and shark skins, we here propose biomimetic designs of various blades with the bio-inspired grooves, aiming at the improvement of the aeroacoustic performance. Based on a systematic study with computational fluid dynamic analyses, we found that these designs had the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Figure 3(a) illustrates the experimental setup comprising various testing facilities conforming to the instructions of JIS (Japan Industrial Standard) B8330. More details of the experimental methods can be found in Wang et al [47]. Here, the aerodynamic efficiency is given by,…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Figure 3(a) illustrates the experimental setup comprising various testing facilities conforming to the instructions of JIS (Japan Industrial Standard) B8330. More details of the experimental methods can be found in Wang et al [47]. Here, the aerodynamic efficiency is given by,…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The structure of spanwise riblet inspired by sharkskin has been applied to simulate the hydrodynamic noise of the three-dimensional (3D) hydrofoil and the maximum noise reduction was observed at 7.28 dB. 84 The blade bionic groove design proposed by J. Wang, Nakata, and Liu 203 was applied to the mixed flow fan and it was found that the use of the groove structure has the potential to suppress noise. When the aerodynamic efficiency loss is only 0.3 percentage points, the blade leading edge reduces the turbulent flow energy by about 38%.…”
Section: Applicationsmentioning
confidence: 99%
“…The high-order compact flow solver was implemented in which the grid was generated through three different methods, including the standard second-order method, the compact scheme, and the Theodorsen technique. The distributions of pressure coefficient C p = 2(p − p ∞ )/ρu 2 ∞ and skin friction coefficient C f = 2τ w /ρu 2 ∞ on the airfoil surface are respectively represented in Figure 11a,b for the subsonic, laminar flow (see, for example, [49][50][51]) with Ma = 0.5 and Re = 10 × 10 3 . The fourth-order compact grid generation method shows improvements in both pressure and skin friction coefficients compared to the second-order method and presents an excellent agreement with those results obtained from the Theodorsen grid generation technique.…”
Section: The Effect Of the Grid Accuracy On Flow Solutionsmentioning
confidence: 99%